2012
DOI: 10.1111/j.1365-2486.2012.02779.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate, duration, and N placement determine N2O emissions in reduced tillage systems: a meta‐analysis

Abstract: No-tillage and reduced tillage (NT/RT) management practices are being promoted in agroecosystems to reduce erosion, sequester additional soil C and reduce production costs. The impact of NT/RT on N2 O emissions, however, has been variable with both increases and decreases in emissions reported. Herein, we quantitatively synthesize studies on the short- and long-term impact of NT/RT on N2 O emissions in humid and dry climatic zones with emissions expressed on both an area- and crop yield-scaled basis. A meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
249
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(286 citation statements)
references
References 102 publications
34
249
2
1
Order By: Relevance
“…However, some authors recorded higher N 2 O emissions under reduced tillage compared to the conventional plough tillage (Mangalassery et al 2014). Van Kessel et al (2013) showed that on clay soils, after changing over from conventional to reduced tillage, N 2 O emissions increased significantly in the initial period of up to 10 years. After 10 years of reduced tillage, they observed a significant decrease in the emissions compared to plough cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors recorded higher N 2 O emissions under reduced tillage compared to the conventional plough tillage (Mangalassery et al 2014). Van Kessel et al (2013) showed that on clay soils, after changing over from conventional to reduced tillage, N 2 O emissions increased significantly in the initial period of up to 10 years. After 10 years of reduced tillage, they observed a significant decrease in the emissions compared to plough cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the methods of reduced tillage appear in agriculture, which, on the one hand, improve soil structure and lower its temperature, thereby limiting greenhouse gas emissions. On the other hand, they increase soil moisture and improve the soaking up of water, which creates anaerobic conditions and is particularly conducive to N 2 O emissions (van Kessel et al 2013, Akbolat et al 2016.…”
mentioning
confidence: 99%
“…That increase could offset the amount of C sequestered under reduced tillage and no-tillage, since N 2 O has a global warming potential 298 times greater than CO 2 (Six et al 2004). However, recent works have found lower N 2 O emissions when no-tillage is practiced in the long term due to a reduction of anaerobic microsites in the soil (Plaza-Bonilla et al 2014;van Kessel et al 2013). These last aspects indicate that future research must take into account the whole C footprint associated to the long-term effects of agricultural practices on greenhouse gas emissions in dryland soils, taking advantage of long-term field experiments and properly validated models.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 99%
“…The meta-analysis of van Kessel et al (2013) reported a significant mitigation of N2O emissions under NT in dry climates and long-term (>10 years) studies. Lower emissions following longterm adoption ofNT were explained as a result of the improvements of SOC content and porosity, thus reducing the formation of anaerobic microsites (Six et al, 2004).…”
Section: Effect Of Campaign Tillage and Crop Systems On N2o Emissionsmentioning
confidence: 99%
“…Pelster et al, 2011;Dendooven et al, 2012;Ball et al, 1999;Yonemuraet al, 2014) due to interaction of tillage with several factors, e.g. soil type, climatic conditions (which determine the prevalence of nitrification or denitrification), nitrogen (N) fertilization rate, crop residues (type and management), and the duration of experiments (van Kessel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%